2019
DOI: 10.1002/jso.25670
|View full text |Cite
|
Sign up to set email alerts
|

Is papillary thyroid microcarcinoma a biologically different disease? A propensity score‐matched analysis

Abstract: Background Papillary thyroid microcarcinoma exhibits an indolent clinical course and could be a candidate for active surveillance in the appropriate setting. It remains unknown whether papillary microcarcinoma is biologically different from larger papillary carcinoma >1 cm. Methods We analyzed clinicopathological information and transcriptome data of papillary thyroid cancer samples from The Cancer Genome Atlas. Propensity‐score matching was used to construct a matched cohort consisting of 29 microcarcinomas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…To reinforce our results, the thyroid cancer (THCA) data set of The Cancer Genome Atlas (TCGA) was analysed [22]. The mRNA expression of CHI3L1 was positively associated with extrathyroidal extension (p < 0.001, Figure 1C), lymph node metastasis (p < 0.001), and TNM stage (p < 0.001).…”
Section: High Chi3l1 Expression Is Associated With a Greater Recurrensupporting
confidence: 58%
“…To reinforce our results, the thyroid cancer (THCA) data set of The Cancer Genome Atlas (TCGA) was analysed [22]. The mRNA expression of CHI3L1 was positively associated with extrathyroidal extension (p < 0.001, Figure 1C), lymph node metastasis (p < 0.001), and TNM stage (p < 0.001).…”
Section: High Chi3l1 Expression Is Associated With a Greater Recurrensupporting
confidence: 58%
“…There is strong evidence that multifocality is a marker of extensive disease instead of an independent prognostic factor for PTC 9 . However, it is necessary to investigate the clinical and prognostic implications of multifocality on PTMC, based on the consensus that PTMC has different genetic characteristics, 21 biological behaviour and corresponding clinical management compared with PTC 10,11 . In fact, some studies have focused on the role of multifocality and its bilaterality in the aggression and prognosis of PTMC 7,8,12,13,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…and UFD PTMC patients matched for propensity scores different genetic characteristics, 21 biological behaviour and corresponding clinical management compared with PTC. 10,11 In fact, some studies have focused on the role of multifocality and its bilaterality in the aggression and prognosis of PTMC.…”
Section: Ta B L E 3 Comparison Of Aggressive Variables Between B-mfd or U-mfdmentioning
confidence: 99%
“…Most authors agree that mPTCs are not "early stage" PTCs, but rather they constitute old lesions that are prone to remain quiescent for years. In fact, even though mPTCs are usually considered to be histologically and biologically similar to PTCs, two groups [3,4] showed that mPTCs display a different gene expression pattern from PTCs and hypothesised that tumour microenvironment could play a role in this phenotypic divergence.…”
Section: Introductionmentioning
confidence: 99%